Aporte de Piaget en la física (Físico-matemáticas) (2023)
This research focuses on improving educational strategies at all levels, not just university education, by addressing common challenges in teaching in general, including lower school levels. The importance of this study lies in its exploration of how Jean Piaget's theories, originally conceived to understand children's cognitive development, have had a positive impact on education as a whole by promoting more active and participatory pedagogical approaches. This not only facilitates a better understanding of concepts, but also stimulates student motivation and the development of critical thinking skills at all educational levels, which is essential to prepare students for the challenges of an ever-changing world. In summary, this research highlights the importance of adapting educational practices at all levels to provide higher quality and more relevant education.